Empowering ulul albab teacher trainees through qei module training / Zulkarnin Zakaria - Zakaria, Zulkarnin (Universiti Teknologi MARA Cawangan Pahang, 2020)
This quantitative study focused on a new batch of teacher trainees who went through the soft skill and personal development modules developed by the Ulul Albab Centre in Universiti Pendidikan Sultan Idris (UPSI). This paper analysed the impact of QEI (Quranic, Encyclopaedic and Ijtihadik) modules on the participants of Ulul Albab Centre (PUA) programme in the university, and examined the attitudes of the programme’s participants towards this new module in their campus life as a university student and individual. The QEI module covers leadership and soft skills which are identified as vital qualities needed for future educators. A standard questionnaire was distributed to the first batch of programme participants of 150 students after they completed the first year of programme. The data was further analysed using the SPSS software and discussed in the final report of the study. The findings revealed that a high percentage of participants believed the modules taught gave constructive impact on their personal development and soft skills and they had positive attitude and high satisfaction rate with the implementation of the Ulul Albab programme. The results would encourage improvements and new ideas to the existing modules as participants shared their comments and suggestions as discussed in this paper